1990
DOI: 10.1159/000100201
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Stereotaxy in the Treatment of Essential Tremor

Abstract: In patients with severe tremor that is resistant to drug therapy, stereotactic coagulation can achieve a satisfactory and lasting reduction of the movement disorders. Very few long-term studies have been conducted following stereotactic operations. From 1964 to 1984, 104 patients with a diagnosis of essential tremor were operated on in the Division of Stereotaxy and Neuronuclear Medicine. After an average follow-up period of 8.6 years, 65 patients were examined. In 80%, the success of the stereotactic operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 9 publications
2
52
0
2
Order By: Relevance
“…Five series have evaluated the effectiveness of VIM thalamotomy for treatment of ET since 1980 [5][6][7][8][9]. In the largest series, Mohadjer et al [5] reported 93.7% immediate improvement after stereotactic thalamotomy in 105 ET patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five series have evaluated the effectiveness of VIM thalamotomy for treatment of ET since 1980 [5][6][7][8][9]. In the largest series, Mohadjer et al [5] reported 93.7% immediate improvement after stereotactic thalamotomy in 105 ET patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although ET occurs more frequently than Parkinson's disease, the number of patients referred for surgery is relatively small. Only a few studies have focused on surgical treatment of ET, and long-term results of stereotactic VIM thalamotomy in patients with ET are not well represented in the literature [5][6][7][8][9]. We have summarized our experience with stereotactic VIM thalamotomy for treatment of medically intractable ET and present here our results from a series of 43 thalamotomies performed in 37 patients.…”
mentioning
confidence: 99%
“…This might suggest some lasting effect since it may be assumed that the patients at baseline had a more severe tremor in the treated hand. In the literature, beneficial results have also been reported in long-term evaluations [17][18][19][20][21][22][23][24][25][26][27]. In some patients the tremor has not been shown to recur during the follow-up time [22].…”
Section: Discussion Tremormentioning
confidence: 92%
“…The most frequently described side effects included cerebellar complications such as speech difficulties (dysarthria, dysphasia, hypophonia), dysequlibrium, apraxia, ataxia, and gait disturbances, as well as contralateral weakness, most probably due to affection of the internal capsule [3, 19, 21-24, 26, 27, 29-33]. Facial numbness and weakness as well as cognitive impairment have also been described [19,20,27,34].…”
Section: Side Effectsmentioning
confidence: 99%
“…Medications are often considered to be effective in only 50% of patients [2]. When the disorder becomes resistant to medication, surgical options for such patients are either ablative procedures such as thalamotomy [17,18] or DBS [19]. Although thalamic DBS has been shown to be a safe and effective therapy in ET patients followed for up to 13 years [20], ET cases exist where DBS failed to produce symptomatic or functional improvement.…”
Section: Introductionmentioning
confidence: 99%